Построение признаков распознавания акустических сигналов - Анохин, М. А.; Дзыма, О. Н. (My University, 2018)
This report is devoted to the most problematic and paramount task in the recognition of acoustic signals – to the choice of recognition signs. From one side acoustic signals should be described with signs carefully when the number of signs is big. From another side the big number of them needs lots of time to process signals and recognize them. In the report will be presented the algorithm of signal compression by the orthogonal transformation signals preliminary transformed into a frequency domain.
Keywords: акустический сигнал